Isolation, Characterization and Identification of Bacillus Species Toxic to Dengue Vector: Identification of Bacillus Sp. (Biological Sciences - PJSIR, 2022)
The work reported in this article was carried out to screen different samples collected from Lahore to isolate bacteria with larvicidal activity against third instar Aedes agypti larvae.Seventy-three bacterial isolates were collected from soil samples, water samples, soil conditioners and insects. Heat treated samples were used for the isolation of spore forming bacteria through spread plate technique. Isolated bacteria were identified as Bacillus thuringiensis, B. laterosporus, B. circulans, B. sphaericus, B. megaterium, B. subtilis and B. alvei by morphological and biochemical testing. Preliminary bioassays were conducted under laboratory conditions to assess the toxicity and efficacy of microbial isolates. Out of seventy three bacterial isolates only one showed ento-mopathogenic activity against Aedes agypti larvae. Isolate with larvicidal activity (CEPS-56) was identified as B. thuringiensis which was isolated from dead mosquito. Toxic isolate of B. thuringiensis (CEPS-56) may be further investigated at the molecular level and effective toxic concentration of CEPS-56 determined by conducting concentration bioassay. The results lead to the conclusion that ento-mopathogenic bacteria are present in natural environment of Lahore and screening of more number of samples may yield different and even more toxic strains of bacteria.Importance. There are no two opinions about the fact that Dengue has caused a havoc in terms of both mortality and morbidity all over the globe particularly in the Asian countries. The social cost of its control is very high. Thus, it is obligatory for the global community to develop different techniques to eradicate it. The research presented here presents a newly discovered technique based on producing toxins by growing bacteria that kill Dengue virus. The study reports the discovery of a strain of Bacillus subtilis and signals towards further exploration of other bacterial strains that can be used to control dengue vector in different parts of the world.